Analysis of Mycobacterium ulcerans-specific T-cell cytokines for diagnosis of Buruli ulcer disease and as potential indicator for disease progression. - Norman Nausch; Daniel Antwi-Berko; Yusif Mubarik; Kabiru Mohammed Abass; Wellington Owusu; Ellis Owusu-Dabo; Linda Batsa Debrah; Alexander Yaw Debrah; Marc Jacobsen; Richard O Phillips (Public Library of Science (PLoS), 2017)
BACKGROUND:Buruli ulcer disease (BUD), caused by Mycobacterium (M.) ulcerans, is the third most common mycobacterial disease after tuberculosis and leprosy. BUD causes necrotic skin lesions and is a significant problem for health care in the affected countries. As for other mycobacterial infections, T cell mediated immune responses are important for protection and recovery during treatment, but detailed studies investigating these immune responses in BUD patients are scarce. In this study, we aimed to characterise M. ulcerans-specific CD4+ T cell responses in BUD patients and to analyse specific cytokine-producing T cells in the context of disease severity and progression. METHODOLOGY/PRINCIPAL FINDINGS:For this case-control study, whole blood samples of BUD patients (N = 36, 1.5-17 years of age) and healthy contacts (N = 22, 3-15 years of age) were stimulated with antigen prepared from M. ulcerans and CD4+ T cells were analysed for the expression of TNFα, IFNγ and CD40L by flow cytometry. The proportions and profile of cytokine producing CD4+ T cells was compared between the two study groups and correlated with disease progression and severity. Proportions of cytokine double-positive IFNγ+TNFα+, TNFα+CD40L+, IFNγ+CD40L+ (p = 0.014, p = 0.010, p = 0.002, respectively) and triple positive IFNγ+TNFα+CD40L+ (p = 0.010) producing CD4+ T cell subsets were increased in BUD patients. In addition, TNFα+CD40L-IFNγ- CD4+ T cells differed between patients and controls (p = 0.034). TNFα+CD40L-IFNγ- CD4+ T cells were correlated with lesion size (p = 0.010) and proportion were higher in 'slow' healers compared to 'fast healers' (p = 0.030). CONCLUSIONS:We were able to identify M. ulcerans-specific CD4+ T cell subsets with specific cytokine profiles. In particular a CD4+ T cell subset, producing TNFα but not IFNγ and CD40L, showed association with lesion size and healing progress. Further studies are required to investigate, if the identified CD4+ T cell subset has the potential to be used as biomarker for diagnosis, severity and/or progression of disease.